Potential Role of Cytochrome c and Tryptase in Psoriasis and Psoriatic Arthritis Pathogenesis: Focus on Resistance to Apoptosis and Oxidative Stress - Chimenti, Maria Sole; Sunzini, Flavia; Fiorucci, Laura; Botti, Elisabetta; Fonti, Giulia Lavinia; Conigliaro, Paola; Triggianese, Paola; Costa, Luisa; Caso, Francesco; Giunta, Alessandro; Esposito, Maria; Bianchi, Luca; et al. (Frontiers in Immunology, 2018)
Psoriasis (PsO) is an autoimmune disease characterized by keratinocyte proliferation, chronic inflammation and mast cell activation. Up to 42 % of patients with PsO may present psoriatic arthritis (PsA). PsO and PsA share common pathophysiologic mechanisms: keratinocytes and fibroblast-like synoviocytes are resistant to apoptosis, this is one of the mechanism facilitating their hyperplastic growth, and, at joint level, the destruction of articular cartilage and bone erosion and/or proliferation. Several clinical studies regarding diseases characterized by impairment of cell death, either due to apoptosis or necrosis, reported cytochrome c release from the mitochondria into the extracellular space and finally into the circulation. The presence of elevated cytochrome c levels in serum has been demonstrated in diseases as inflammatory arthritis, myocardial infarction and stroke, and liver diseases. Cytochrome c is a signalling molecule essential for apoptotic cell death released from mitochondria to the cytosol allowing the interaction with protease, as the apoptosis protease activation factor (APAf-1), which lead to the activation of factor-1 and procaspase 9. It has been demonstrated that this efflux from the mitochondria is crucial to start the intracellular signalling responsible for apoptosis, then to the activation of the inflammatory process. Another inflammatory marker, the tryptase, a trypsin-like serine protease produced by mast cells, is released during inflammation, leading to the activation of several immune cells through proteinase-activated receptor-2. In this review, we aimed at discussing the role played by cytochrome c and tryptase in PsO and PsA pathogenesis. To this purpose, we searched pathogenetic mechanisms in PUBMED database and review on oxidative stress, cytochrome c and tryptase and their potential role during inflammation in PsO and PsA. To this regard, the cytochrome c release into the extracellular space and tryptase may have a role in skin and joint inflammation.